FOREIGN LANGUAGE LEARNING REFORMS - B.M.Xojaniyazova; M.Q.Allaberdiyeva (Лучшие интеллектуальные исследования, 2024)
This article provides a comparative analysis of foreign language learning methods. The development of modern science today is inconceivable without technology, modern computers, and information technology.